Keanekaragaman dan dominansi superclass pisces di pesisir Kabupaten Pasuruan sebagai bahan ajar pada materi keanekaragaman hayati kelas x - Wanandi, Ichsan Bakhtiar; Nugroho, Endik Deni (Jurnal Pendidikan Biologi Undiksha, 2023)
Indonesia is an archipelagic country with the highest level of biodiversity after Brazil. The diversity of Superclass Pisces (fish) in Indonesia is very significant. Indonesia's coastal resources are the centre of the richest tropical marine biodiversity in the world, where 90% of the fish catch comes from coastal waters within a 12 nautical mile radius of the coastline. From the data obtained, seafood from the coast of Pasuruan Regency is relatively abundant. In Kalirejo Village, Kraton District, most residents work as fishermen. Fishermen in Kalirejo Village usually look for fish on the coast of Pasuruan Regency. The fish obtained were dominated by ilat-ilatan fish (tongue fish). In the southern part of the coast of Pasuruan Regency, to be precise, from the Kalirejo Village area, Kraton District, there has been no research on the diversity and dominance of Superclass Pisces in the Madura Strait waters as well as a local potential that can be used as teaching materials. Local potential can be associated with learning, especially in learning Biology as a learning resource. Utilization of the local potential of the Superclass Pisces in the Madura Strait Waters can potentially become teaching material in biology lessons in high schools, especially in the CP (Learning Outcomes) of the Diversity of Living Things and Their Role in the subject of Diversity with the scope of the Spread of Fauna in Indonesia. Therefore, researchers are interested in conducting a research entitled "Diversity and Dominance of Superclass Pisces on the Coast of Pasuruan Regency as Potential Teaching Materials. Based on the research results, analysis of the diversity index of Superclass Pisces showed a diversity index of 1.666 and an evenness index of 0.9. With the acquisition of this diversity value, it has moderate criteria, which means sufficient productivity, fairly balanced ecosystem conditions and moderate ecological pressure consisting of 6 families and 7 species. The results of the dominance index analysis showed a diversity index of 0.22. With the acquisition of diversity values, it has low dominance criteria. The total number of fish found on the coast of Pasuruan Regency most commonly found were Cynoglossus lingua with 8 individuals, Johnius trachycephalus and Rastrelliger kanagurta with 7 individuals, Mystus Sinaringan and Scatophagus argus with 2 individuals, and Rastrelliger faughni and Sphoeroides pachygaster with 1 individual. Based on the research results, there was a link between research results and learning biology on biodiversity material, so it can be used as teaching material based on local potential. Keywords: Diversity, Dominance, Superclass Pisces, Coastal District of Pasuruan, and Local Potential